The Effect of Industrial Noise Exposure on Hypertension Incidence Among Factory Workers in Surabaya - Sholihah, Puput Mar'atus; Setyawan, Yuswanto (Universitas Mohammad Husni Thamrin, 2025)
In Surabaya, as one of Indonesia's industrial centers, many factory workers are exposed to high noise levels daily. However, specific data on the relationship between industrial noise exposure and hypertension incidence among factory workers in Surabaya is still limited. This study aims to assess the association between industrial noise exposure and hypertension among factory workers in Surabaya. This study aims to assess the association between industrial noise exposure and hypertension among factory workers in Surabaya. The collected data were analyzed using appropriate statistical tests, such as the Chi-Square test and Spearman correlation. The Spearman correlation analysis indicates that industrial noise exposure contributes to a 62% increase in the incidence of hypertension among factory workers in Surabaya, particularly affecting women at a higher rate than men. Higher noise levels correlate with a greater risk of developing hypertension. Noise from factory machinery also increases hypertension risks more significantly among female workers and employees over 40 years old, regardless of gender. Keywords; Industrial noise exposure; Hypertension; Factory workers